An optimisation study for catalytic hydrolysis of oil palm shell using response surface methodology - Sabzoi, N.; Yong, E.K.; Jayakumar, N.S.; Sahu, J.N.; Ganesan, P.; Mubarak, N.M.; Mazari, S.A. (2015)
Oil palm shell has great potential for conversion to biofuels because of its abundance and favourable composition. Catalytic hydrolysis of oil palm shell was performed using sodium hydroxide as a catalyst. The main objective of the study was to optimise the process parameters for yield percentage of bio-oil from catalytic hydrolysis of palm shell by means of response surface methodology with central composite design. The parameters investigated were reaction temperature (140 degrees C-230 degrees C), reaction time (10-30 min) and NaOH concentration (04 m-1.5 m). The main product (bio-oil) was characterised using Fourier transform infra-red spectroscopy and the bomb calorimeter to find the functional groups and higher heating value of bio-oil. Among all the three parameters, the NaOH concentration was found to be the most influencing factor for liquid yield percentage followed by reaction temperature and time, respectively. The R-squared value of the model was 0.9657 indicating an excellent match for values of liquid production in predicted and experimental results. The optimum conditions found were: temperature at 230 degrees C, time at 10 min, and NaOH concentration at 1.5 M yielded 74.6 wt.% of product. The heating values determined for acetone and water-soluble products at optimum conditions were 22.4 MJ kg(-1) and 14.3 MJ kg(-1).